Education on the Use of Hydrogels to Grow Ornamental Plants: Building Environmental Awareness since an Early Age (SB Sentul Kuala Lumpur, Malaysia) - Nun Maulida Suci Ayomi; Ali Khamdi; Nurul Puspita (Jurnal Pengabdian Masyarakat Waradin, 2025)
The purpose of this community service activity are to introduce hydrogel planting media and provide knowledge about ornamental plants that can be recommended to students at Sanggar Belajar Sentul, Kuala Lumpur, Malaysia. The fulfillment of the material target, the level of enthusiasm of the participants, and the ability of the participants to take part in planting training using hydrogel planting media-which involves the reuse of used bottles for ornamental plants are the three main achievements of the community service activities that have been carried out.